Ultrasound-assisted swelling of bacterial cellulose - Song, J. (2017)
Bacterial cellulose (BC) was obtained by static cultivation using commercial BC gel from scoby. BC membranes (oven dried and freeze-dried) were swelled with 8% NaOH, in absence and in presence of ultrasound (US), for 30, 60 and 90 min. The influence of swelling conditions on both physico-chemical properties and molecules entrapment was evaluated. Considering the highest levels of entrapment, an optimum swelling procedure was established: 8% NaOH for 30 min. at room temperature in the presence of US. Native and PEGylated laccase from Myceliophthora Thermophila was immobilized on BC membranes and a different catalytic behaviour was observed after immobilization. Native laccase presented activity values similar to published reports (5-7 U/gBC) after immobilization whereas PEGylated enzymes showed much lower activity (1-2 U/gBC). BC swelled membranes are presented herein as a potential support for the preparation of immobilized enzymes for industrial applications, like phenolics polymerization.